Long wave infrared intersubband quantum devices - Jin,Yuhao (Nanyang Technological University, 2024)
Mid-infrared (MIR) region has demonstrated its great potential in numerous applications, including but not limited to spectroscopy, thermal imaging, and free space communications. Long wave infrared (LWIR), which is typically defined as 8 to 20 µm, is part of the MIR range. In the LWIR region, there are remarkable applications which are not accessible in other bands of the MIR range. For example, the sensing of the molecules showing strong and unique absorption features, like benzene, toluene, ethylbenzene, and o-xylenes (BTEX); the detection of cool objects via thermal imaging. However, due to the lack of high performance laser sources and detectors, the LWIR range is far from fully explored. Recently, due to the high efficiency and the flexibility in the design of operation wavelength, the quantum devices based on the intersubband transition have attracted more attention in the LWIR range, especially for the devices such as quantum cascade laser (QCLs) and quantum cascade detectors (QCDs). In this thesis, the LWIR laser sources have been investigated. Considering the challenges of extending the wavelength of QCLs from the mature range to LWIR, the improved high optical gain active region based on the diagonal transition and three-phonon-resonance design has been experimentally demonstrated. The proposed LWIR QCL device has realized high peak power at room temperature. Based on such active region design, a tunable single-mode slot waveguide QCL array has also been developed, and the multi-gases spectroscopy measurements have been done, which establish the capability of proposed LWIR QCLs for practical applications. High power laser source with good beam quality is highly desirable for most of the applications in the MIR range. Due to the performance degradation of the LWIR QCLs, the power scaling of coherent emission is attractive. Thus, the phase-locked QCL array based on supersymmetry has been designed and achieved in the experiment. The stable near-diffraction-limited emission has been observed during the whole dynamic range, which is consistent with the simulation results. Motivated by the dark current-less properties of QCDs, such kind of photovoltaic device shows the potential of high temperature operation, where most of the photodetectors in the LWIR range are limited to the cryogenic temperature. Here the design and experimental results of the LWIR QCD based on bound-to-miniband diagonal transition are presented. The preliminary results and findings could pave the way toward LWIR room temperature QCDs.